Teoria clássica e medieval da composição epistolar : entre epistolografia e retórica - Ramos, Manuel (2017)
I will try to approach the question concerning the theory of letter writing during classical and medieval periods among a wide variety of ways of approaching this topic. This study will refer not only to the different uses of the letter, but also to the different kinds of letters, their patterns, their appropriateness to the receivers status, the question of the style used, among many other features. We will try to show that the theory of letter writing was never very far from the theory of speech composing during the classic period, but it was during medieval period that the connection between the two areas of knowledge became closer, since letter writing was strongly influenced by the rhetoric and it evolved as a part of this topic. This theory necessarily implies presenting some of the treaties on letter writing and the authors who cultivated this theme.